Artificial sphincter BR - SL - AS 904 in the treatment of urinary incontinence after radical prostatectomy: Efficacy, practicality and safety in a prospective and multicenter study - Lima, Salvador Vilar Correia; de Barros, Evandilson Guenes Campos; Vilar, Fabio de Oliveira; Pinto, Flavia Cristina Morone; Barros, Thomé Décio Pinheiro; Truzzi, José Carlos; de Toledo, Luiz Gustavo M.; Kanasiro, Francisco; Amaro, João Luiz [UNESP] (FapUNIFESP (SciELO), 2018)
Purpose: The objective of the present study is to test the efficiency and practicality of a new artificial sphincter BR - SL - AS - 904 in the control of urinary incontinence in post - PR patients and to evaluate their complications. Patients and Methods: Fifteen patients with incontinence after one year of radical prostatectomy were included prospectively. All patients underwent artificial urethral sphincter (AUS) implant BR - SL - AS - 904 according to established technique. Independent variables such as free urinary flow, PAD weight test, ICIQ - SF score and urinary symptoms through the IPSS score were compared in different follow-up moments. Results: Patients submitted to AUS implantation did not present trans - operative or post - operative complications related to the surgical act such as: infection, hematoma, erosion or urinary retention. Device was inert to the body during the follow-up, showing an excellent adaptation of the patients, besides the easy handling. The mean age was 68.20 years 40% of the patients had systemic arterial hypertension, 6.7% diabetes mellitus, 6.7% were hypertensive and diabetic, 13.4% were hypertensive, had diabetes and hypercholesterolemia and 26.7% patients had no comorbidities. It was evidenced that the urinary flow peak during the follow-up remained stable. Decreased averages and median PAD weight test were 135.19 to 75.72 and 106.00 to 23.50, respectively. The IPSS score decreased and the quality of life increased (12.33 to 3.40 and 2.50 to 3.20 respectively). The ICQF - SF questionnaire score also showed a decrease, ranging from 16, 71 to 7.33. Conclusion: The artificial sphincter implant BR - SL - AS 904 was reproducible, safe and effective in the control of urinary incontinence in post - PR patients.
Keywords: Artificial; Prostatic neoplasms; Urinary incontinence; Urinary sphincter